The numerical solution of interacting air jets problem for low Reynolds numbers - Eren, Haydar; Peremeci, Ömer Erkin; Tanyildizi, Vedat (My University, 1998)
The problem of interaction of jets is one of the interesting research subjects in the engineering applications. In this work, the two dimensional flow field resulting from the interaction of two jets perpendicular to each other is investigated numerically. In the study, the exit velocity and pressure distributions for both of the jets are chosen as the same. The finite difference equations are obtained by applying the Crank-Nicholson implicit method to the non-dimensional equations of motion written for the unsteady flow of the compressible fluids; and the flow behaviors in the interaction region is investigated by solving those equations for Re=0.5 and Re=25 with a computer program coded in Fortran 77. It is seen from the results that the flow is mixed and the negative velocities are magnified and the flow is rotational in the intersection region.
Hava jetleri girisimi probleminin dusuk Reynolds sayilarinda cozumu icin sayisal bir yontem
Keywords: air jet; interaction; jet flow; laminar flow; jet; laminar flow